.

 

89

y =
1 D(y) = ( ; 1)( 1; 1)(1; + )
2 1
= ; = +
= ; = +
x = 1
3 y = kx + b
k = == == 1
b = () = + x= == = == 0
y = x x
4
5 f(x) = = = f(x)
6 y = 0; = 0; x = 0
OY
y(0) = 0
OX
x = 0
> 0
y > 0 x ( ; 1)(0; 1)
y < 0 x ( 1; 0)( 1; + )
7 y=
y= 0
=== 0
x( x+3) = 0
x = 0; x = 1,73
y x = 1


x

( ; 1,73)

- 1,73

(-1,73;-1)

( 1; 0)

0

(0; 1)

(1;1,73)

1,73

( 1,73; + )

y

0

+

+

0

+

+

0

y

2,6

0

2,6

 

8 y= =
= = = =
y= 0; 2x(x+3) = 0; x = 0
y x = 1


x

( ; 1)

( 1; 0)

0

(0; 1)

( 1; + )

y

+

0

+

y

0


9 E(y) = R
10


x

3

2

1,5

0,5

0

0,5

1,5

2

3

y

3,4

2,7

2,7

0,17

0

0,17

2,7

2,7

3,4